IMPROVING TAX COMPLIANCE OF THE CONSTRUCTION SECTOR IN INDONESIA: A JURIDICAL PERSPECTIVE - Anis W. Hermawan (Scientia Integritas Utama, 2022)
Data in the form of summary statistics of construction companies, the number of individual construction businesses, the occurrence of fictitious subcontractors and/or borrow-to-use companies, and other potential frauds that can occur in the construction services sector can create tax potentials that can have a double effect on tax revenue in Indonesia. Based on normative juridical studies, two main conclusions are drawn. First, the tax regulation in the construction services business sector has not yet synergized the KUP Law, the Income Tax Law, the VAT Law, and the Construction Services Law. Second, efforts to improve construction services must be carried out through understanding the occurrence of several modes, such as fictitious or borrowing subcontractors and litigation and non-litigation disputes in the construction services sector, which are synergized at least with the KUP Law, Income Tax Law, the VAT Law, and the Construction Services Law. It is recommended that the Tax Authority actively use Article 35 A of the KUP Law in requesting data on information from litigation and non-litigation agencies related to the construction services sector, proving Fictitious or loan-use Subcontractors, and carefully applying positive corrections to costs following Article 6 paragraph (1) letter The Income Tax Law simultaneously imposes Article 23 Income Tax Objects on gifts in any name and form for transactions related to Fictitious Subcontractors or saving-use companies if Government Regulation Number 9 of 2022 is not enacted yet.